Unbalanced production of LTB4/PGE2 driven by diabetes increases susceptibility to cutaneous leishmaniasis - Icaro Bonyek-Silva; Sara Nunes; Reinan L. Santos; Filipe R. Lima; Alexsandro Lago; Juliana Silva; Lucas P. Carvalho; Sergio M. Arruda; Henrique C. Serezani; Edgar M. Carvalho; Claudia I. Brodskyn; Natalia M. Tavares (Emerging Microbes and Infections)
Poorly controlled diabetes mellitus leads to several comorbidities, including susceptibility to infections. Hyperglycemia increases phagocyte responsiveness, however immune cells from people with diabetes show inadequate antimicrobial functions. We and others have shown that aberrant production of leukotriene B4 (LTB4) is detrimental to host defense in models of bacterial infection. Here, we will unveil the consequences of high glucose in the outcome of Leishmania braziliensis skin infection in people with diabetes and determine the role of LTB4 in human phagocytes. We show that diabetes leads to higher systemic levels of LTB4, IL-6 and TNF-α in cutaneous leishmaniasis. Only LTB4 correlated with blood glucose levels and healing time in diabetes comorbidity. Skin lesions of people with leishmaniasis and diabetes exhibit increased neutrophil and amastigote numbers. Monocyte-derived macrophages from these individuals showed higher L. braziliensis loads, reduced production of Reactive Oxygen Species and unbalanced LTB4/PGE2 ratio. Our data reveal a systemic inflammation driven by diabetes comorbidity in opposition to a local reduced capacity to resolve L. braziliensis infection and a worse disease outcome.